Sonic Hedgehog and Triiodothyronine Pathway Interact in Mouse Embryonic Neural Stem Cells - Ostasov, Pavel; Tuma, Jan; Pitule, Pavel; Moravec, Jiri; Houdek, Zbynek; Vozeh, Frantisek; Kralickova, Milena; Cendelin, Jan; Babuska, Vaclav (International journal of molecular sciences, 2020)
Neural stem cells are fundamental to development of the central nervous system (CNS)-as well as its plasticity and regeneration-and represent a potential tool for neuro transplantation therapy and research. This study is focused on examination of the proliferation dynamic and fate of embryonic neural stem cells (eNSCs) under differentiating conditions. In this work, we analyzed eNSCs differentiating alone and in the presence of sonic hedgehog (SHH) or triiodothyronine (T3) which play an important role in the development of the CNS. We found that inhibition of the SHH pathway and activation of the T3 pathway increased cellular health and survival of differentiating eNSCs. In addition, T3 was able to increase the expression of the gene for the receptor smoothened (Smo), which is part of the SHH signaling cascade, while SHH increased the expression of the T3 receptor beta gene (Thrb). This might be the reason why the combination of SHH and T3 increased the expression of the thyroxine 5-deiodinase type III gene (Dio3), which inhibits T3 activity, which in turn affects cellular health and proliferation activity of eNSCs.
Keywords: kultivované buňky; embryonic neural stem cells; sonic hedgehog; Neural Stem Cells; tyreoidální hormony, receptory beta; Hedgehog Proteins; proteiny hedgehog; receptor Smoothened; myši inbrední C57BL; myší embryonální kmenové buňky; Mice; jodidperoxidasa; trijodthyronin; Thyroid Hormone Receptors beta; Cells, Cultured; neurogeneze; zvířata; Smoothened Receptor; Neurogenesis; triiodothyronine; cell differentiation; nervové kmenové buňky; Triiodothyronine; myši; Mouse Embryonic Stem Cells; Iodide Peroxidase; Mice, Inbred C57BL; Animals